1988
DOI: 10.1007/bf01798366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rest, stress, and food on myoelectric spiking activity of left and sigmoid colon in humans

Abstract: The great variability which is known to affect colonic motility may partly be the result of changes in physiological conditions. In order to test this hypothesis, 40 subjects were sequentially put in conditions of vigilance, rest, stress, and feeding while colonic motility was monitored. The myoelectric spiking activity of the left colon was recorded with a 50-cm-long silastic tube equipped with four bipolar ring electrodes (located 10 cm apart) introduced into the left colon by flexible sigmoidoscopy. Tracing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…The stimulation of peristalsis up to the rectosigmoid junction by oral sennosides, obtained as a preliminary result, seems to be in agreement with observations after intra colonic administration [11] and for most of the other stimulant laxatives [3][4][5]8], It cor responds probably to contractions aborally propagated over the whole colon, the propul sive mass movements appearing unfrequently [17], first described in fluorographic terms in 1909 by Holzknecht [22], Neverthe less, Ritchie [7] observed with oxyphenisatin an interruption of propagation waves be tween 24 to 40 cm from the anal verge. Moreover, only the motility index was stim ulated by oxyphenisatin infusion in the rec tum [2,11], as in one data on rectosigmoid with bisacodyl [5].…”
Section: Sennoside-induced Colonic Motor Pattern: Nonspecific For Laxsupporting
confidence: 89%
See 2 more Smart Citations
“…The stimulation of peristalsis up to the rectosigmoid junction by oral sennosides, obtained as a preliminary result, seems to be in agreement with observations after intra colonic administration [11] and for most of the other stimulant laxatives [3][4][5]8], It cor responds probably to contractions aborally propagated over the whole colon, the propul sive mass movements appearing unfrequently [17], first described in fluorographic terms in 1909 by Holzknecht [22], Neverthe less, Ritchie [7] observed with oxyphenisatin an interruption of propagation waves be tween 24 to 40 cm from the anal verge. Moreover, only the motility index was stim ulated by oxyphenisatin infusion in the rec tum [2,11], as in one data on rectosigmoid with bisacodyl [5].…”
Section: Sennoside-induced Colonic Motor Pattern: Nonspecific For Laxsupporting
confidence: 89%
“…These findings have been recently confirmed at the sigmoid level (15-25 cm from anal verge) using ma nometry [4] or electromyography [5]. The electromyographic studies revealed a de crease in tonic activity of the colon wall.…”
Section: Laxatives and Human Colonic Motilitymentioning
confidence: 73%
See 1 more Smart Citation
“…Stress susceptibility appears to be especially marked among IBS patients when compared with healthy cohorts or patients suffering from other lower bowel disorders (Kumar and Wingate, 1985). Even among the healthy, acute psychological or physical stress evokes myoelectrical spiking, strong propulsive and nonpropulsive contractions, and pain (Almy and Tulin, 1947;Schang et al, 1988). In rodents, restraint stress stimulates colonic myoelectrical spiking (Gue et al, 1991), accelerates transit (Williams et al, 1987), disrupts the mucosal barrier (Saunders et al, 2002), and increases mucous secretion (Castagliuolo et al, 1998), outcomes that are mediated in part by activation of myenteric neurons and the release of inflammatory mediators (Groot et al, 2000;Soderholm and Perdue, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by some [23, 24], but denied by others [25, 26]. Whereas these data mainly applied to normal subjects, others have explored the difference between IBS patients and normal controls.…”
Section: Influence Of Psychological Factors On Gut Motilitymentioning
confidence: 65%